2022
DOI: 10.3390/atmos13111880
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effects of Drought Using the Crop Moisture Stress as an Indicator of Maize and Sunflower Yield Reduction in Serbia

Abstract: The drought in Serbia in the summer of 2017 heavily affected agricultural production, decreasing yields of maize, sunflower, soybean, and sugar beet. Monitoring moisture levels in crops can provide timely information about potential risk within a growing season, thus helping to create an early warning system for various stakeholders. The purpose of this study was to quantify the level of moisture stress in crops during summer and the consequences that it can have on yields. For that, maize and sunflower yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Undoubtedly, the rainfall factor is a major element in the cultivation of maize [62,63], especially if the rainfall level is defective during certain years or during certain stages of the vegetation period [64]. Moderate moisture from the appearance of the eighth leaf to tillering and from drought to tillering cuts maize yield in half [65]. The production also drops by half when the plants grow in drought conditions until the formation of the first eight leaves, and in moderate humidity conditions until sprouting [66,67], even if they continue to benefit from optimal humidity.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, the rainfall factor is a major element in the cultivation of maize [62,63], especially if the rainfall level is defective during certain years or during certain stages of the vegetation period [64]. Moderate moisture from the appearance of the eighth leaf to tillering and from drought to tillering cuts maize yield in half [65]. The production also drops by half when the plants grow in drought conditions until the formation of the first eight leaves, and in moderate humidity conditions until sprouting [66,67], even if they continue to benefit from optimal humidity.…”
Section: Discussionmentioning
confidence: 99%
“…B. halotolerans was reported to protect plant growth and alleviate salt stress in wheat by modulating phytohormone synthesis and regulating osmotic balance, ion homeostasis, and gene expression [ 85 ]. Another important abiotic stress which leads to negative impact on crop production is agricultural drought as a period of soil moisture deficit resulting from a combination of rainfall deficiency and excessive evapotranspiration in a particular region [ 9 ]. Twenty-one isolates from sugar beets could be classified as drought-tolerant bacteria based on their ability to grow under high moisture deficit stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Drought and high salinities are one of the limiting factors in the growth and productivity of agricultural crops, especially in arid and semi-arid regions. As a natural hazard, drought in Serbia in the summer of 2017 severely affected agricultural production, reducing yields of corn, sunflower, soybeans, and sugar beets between 30 and 60%, while the total loss was estimated at $1.5 billion [ 9 ]. In this regard, it has been reported that PGPBs enhanced tolerance to drought and salt stress of many different crops [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sunflower is a species with a high impact on human food security that is susceptible to drought stress (Smaeili et al, 2022). The problems caused by the sunflower drought are evident not only in the Republic of Moldova, but also in various countries in its geographical vicinity (Harsányi et al, 2021;Mimić et al, 2022). However, in order to sustainably increase sunflower yield and oil quality under drought stress and future climate change, extensive research on the integration of different management options, including agronomic management, traditional breeding, and modern biotechnological advances, is required.…”
Section: Concerns Regarding Sunflower Crops In the Context Of Climate...mentioning
confidence: 99%